EFEKTIVITAS PENGAWASAN BADAN PERMUSYAWARATAN DESA DALAM UPAYA PEMBANGUNAN DESA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - HASANUDIN, MUHAMAD (Peneliti.net, 2024)
The government is a state organization that maintains and exercises its power to regulate and aim for the benefit of the life of its people. Regional autonomy is a concept of organizing government in Indonesia, this is constitutionally regulated in Law Number 23 of 2014 concerning Regional Government. The Village Consultative Body in Telukjaya Village, Pakisjaya District, Karawang Regency, based on its authority in channeling aspirations, of course, needs to consider the efforts that will be made by the village government in realizing community aspirations, as well as monitoring efforts being made. Seeing this is part of village development efforts. The Normative Juridical Method is a scientific method whose research is only shown in written regulations so that this research is very closely related to the library because it will require secondary data from the library. This research is often also called doctrinal research. By using the normative juridical method, it can be analyzed that the effectiveness of the supervision of the Telukjaya Village Consultative Body is targeted at implementing village government planning as the organizer of village development planning. as well as absorbing and channeling community aspirations using a number of methods such as the aspiration box in the village office, interaction with relevant communities and efforts to strengthen communication and coordination between the Village Government and the Village Consultative Body.